Antimicrobial susceptibility and molecular epidemiology of extended-spectrum beta-lactamase-producing Enterobacteriaceae from intensive care units at Hamad Medical Corporation, Qatar. Issue 1 (December 2016) - Sid Ahmed, Mazen; Bansal, Devendra; Acharya, Anushree; Elmi, Asha; Hamid, Jemal; Sid Ahmed, Abuelhassan; Chandra, Prem; Ibrahim, Emad; Sultan, Ali; Doiphode, Sanjay; Bilal, Naser; Deshmukh, Anand
Abstract Background The emergence of extended-spectrum beta-lactamase (ESBL)-producing isolates has important clinical and therapeutic implications. High prevalence of ESBL-producing Enterobacteriaceae has been reported in the literature for clinical samples from a variety of infection sites. The present study was undertaken to evaluate the prevalence of ESBL-producing Enterobacteriaceae, and to perform molecular characterization and antimicrobial susceptibility testing of clinical isolates from patients admitted to the intensive care units at Hamad Medical Corporation, Doha, Qatar, from November 2012 to October 2013. Methods A total of 629 Enterobacteriaceae isolates were included in the study. Identification and susceptibility testing was performed using Phoenix (Becton Dickinson) and the ESBL producers were confirmed by double-disk potentiation as recommended by the Clinical and Laboratory Standards Institute. Molecular analysis of the ESBL producers was performed by polymerase chain reaction. Results In total, 109 isolates (17.3 %) were confirmed as ESBL producers and all were sensitive to meropenem in routine susceptibility assays. Most of the ESBL producers (99.1 %) were resistant to amoxicillin/clavulanic acid and ceftriaxone and 93.6 % were resistant to cefepime. Among the ESBL-producing genes, bla CTX-M (66.1 %) was the most prevalent, followed bybla SHV (53.2 %) andbla TEM (40.4 %). Conclusions These findings show the high prevalence of ESBL-producing Enterobacteriaceae within the intensive care units at Hamad Medical Corporation, Qatar, and emphasize the need for judicious use of antibiotics and the implementation of strict infection control measures.